Ruptured splenic artery aneurysm in late pregnancy - Abraham, A. A.; Abraham, Sally M. (International Journal of Research in Medical Sciences, 2017)
The spontaneous rupture of the spleen in pregnancy is rare and is frequently misdiagnosed. Failure to recognize the condition can be fatal to mother and foetus at least in a peripheral hospital. In the last trimester of pregnancy it is easily confused with rupture of uterus or abruptio placenta.